PENGGUNAAN LIMBAH SERBUK BESI SEBAGAI MATERIAL PENGISI (FILLER) PADA CAMPURAN STRUKTUR PERKERASAN JALAN KOLEKTOR PONCO – JATIROGO (STA.130+200 – STA.138+700) - Nugroho Utomo; Iwan Wahjudijanto; Fitri Sri Rizki Yasin (Envirotek : Jurnal Ilmiah Teknik Lingkungan, 2020)
This research is held as a efforts to improving the strength of road structure and also handling iron powder waste, by using it as a filler on pavements structure mix design at Ponco – Jatirogo (STA.130+200 – STA.138+700). Iron powder filler variations value adding on this research is brought 0%, 12%, 17%, 22% and 27% from total weight of pavements mix. Amount percentage of filler accordingly taken from requirements that is set on General Specifications of Bina Marga Division 6-2010 (Revision 3) about filler material using on road pavements mix provisions. A results of Marshall Test on asphalt mix with filler material variations from iron powder takes the best and fulfill General Specifications of Bina Marga requirements obtained on filler value rate 22% with bath-time 1 hours, which VMA (Void in Mineral Aggregate) value 67,93%, VFA (Void Filled with Aggregate) value 92,91%, VIM (Void In Mix) value 4,82%, stability value 1371,6 kg, flow value 4,77 mm and Marshall Quotient (MQ) value 288,93 kg/mm.